Gravity forward modeling with a tesseroid-based Rock-Water-Ice approach - Theory and applications in the context of the GOCE mission and height system unification - Grombein, Thomas (Schriftenreihe des Studiengangs Geodäsie und Geoinformatik / Karlsruher Institut für Technologie, Studiengang Geodäsie und Geoinformatik, 2017)
Detailed information on the gravitational effect of the Earth's topographic and isostatic masses can be calculated by gravity forward modeling. Within this book, the tesseroid-based Rock-Water-Ice (RWI) approach is developed, which allows a rigorous separate modeling of the Earth's rock, water, and ice masses with variable density values. Besides a discussion and evaluation of the RWI approach, applications in the context of the GOCE satellite mission and height system unification are presented.